Iambos Polytropos: A comparison of the language of Callimachus' Iambi, Archilocus, and Hipponax - FELISARI, CLARA (Trinity College Dublin. School of Histories & Humanities. Discipline of Classics, 2017)
My work analyses the language of Callimachus? Iambi in relation to the languages of the iambographers who precede him, notably Archilochus, and Hipponax. These three iambographers allow significant scope for intertextual research, since it is clear that Callimachus had Archilochus (implicitly) and Hipponax (explicitly) as his two main models while he was composing his Iambi, and the iambic remains of these three authors, despite being frustratingly fragmentary, are substantial enough to allow comparison. The comparison involves both themes and language but focuses on the latter. Chapters 1 and 2 analyse respectively lexicon and morphology, and syntax and pragmatics. Building on them, Chapter 3 explores the iambic themes shared by all three iambographers, and Chapter 4 seeks to explain how the iambographers? language fits their poetic subjects and purposes. Here, I pay particular attention to shifts from the traditional expected poetic form. Using methodologies developed for code-switching in spoken languages, I analyse the linguistic variation that, I contend, is a key characteristic of iambic poetry, ranging from ?moves? such as the substitution of a single word in a well-established Homeric formula, or the change of a word?s grammatical gender or suffix of a word, to shifts of tone, e.g. from hymnic to comic or comic to epic within a short space of words. I contextualise these linguistic (and, often, also thematic) shifts within Callimachus? defence, in Iambus 13, of his poetry?s polye?deia, roughly translatable as ?pluriformity.? This feature is, in fact, not limited to Callimachus? Iambi, but also pertains to the poetry of Archilochus and Hipponax and appears to be a central characteristic of iambic poetry at large. Scholarship has generally regarded the iambic genre as a loose network of poems without fixed shared characteristics. I argue that this is due, paradoxically, to the fact that variety is one of the main features of the genre. Callimachus revives this interest in variety through his Iambi, at a time when the mainstream poetic tradition had reduced iambs to abusive poetry. Furthermore, I suggest that the use of linguistic variety also fits with iambic poetry?s social function: iambic texts have an educational and, especially, moralising purpose, which the later (post-Hellenistic) evidence confirms.
APPROVED